Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1755-6686.2009.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's Disease and Secondary Amyloidosis: Early Complication? A Case Report and Review of the Literature

Abstract: Secondary amyloidosis is a rare but serious complication of inflammatory bowel disease (IBD), generally seen in Crohn's disease. At least 1% of patients with Crohn's disease develop amyloidosis. In the literature, the time lapse between the onset of Crohn's disease and the diagnosis of amyloidosis has been reported to range from one to 21 years. In most patients, proteinuria heralded the onset of renal involvement from amyloid and occurred from three to 15 years after Crohn's disease diagnosis. In this case, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…9,[21][22][23][24][25] There are many case reports on amyloidosis, but reviewing the literature the overall prevalence in IBD seems to be below 1%. 9,21,22 Glomerulonephritis has recently emerged as an extraintestinal manifestation and seems to be very rare with about 40 reports in the literature; it appears to be linked to disease activity as renal function improves after remission of IBD. 9,23,24 Tubulointerstitial nephritis seems to be a common clinical feature among IBD patients, manifesting with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…9,[21][22][23][24][25] There are many case reports on amyloidosis, but reviewing the literature the overall prevalence in IBD seems to be below 1%. 9,21,22 Glomerulonephritis has recently emerged as an extraintestinal manifestation and seems to be very rare with about 40 reports in the literature; it appears to be linked to disease activity as renal function improves after remission of IBD. 9,23,24 Tubulointerstitial nephritis seems to be a common clinical feature among IBD patients, manifesting with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloidosis can appear early in the history of CD, sometimes before diagnosis of CD is made, or years after initial digestive symptoms . Mortality is almost related to renal failure, Wester et al .…”
Section: Hepatic Amyloidosismentioning
confidence: 99%
“…[3] Nevertheless, there are case reports in which amyloidosis is an early initial complication of Crohn's disease. [4] Our case raises the question of how the 'traditional' markers of inflammation could have underestimated the inflammatory burden, as CRP had been below 3 mg dL and colonoscopies had shown mild inflammatory activity in the past 9 years. The reliability of CRP as a marker for inflammation was recently questioned when it was shown that a subset of patients with normal CRP values sometimes had significant mucosal lesions.…”
Section: Discussionmentioning
confidence: 92%